Smart Penataran: Transformasi Digital Desa Wisata Candi Menuju Masyarakat Sejahtera dan Berdaya Saing : Penelitian - Habib Bawafi; Puji Asmaul Chusna; Lailatul Mubarakah; Mada Purwa H.; Kunti Alfi H.; Afif Mustafa (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study analyzes the implementation and impact of the Smart Penataran program in the digital transformation of Penataran Temple Tourism Village towards a prosperous and competitive society. Using a mixed-methods approach with 156 respondents over 8 months (March-October 2025), the study measured improvements in digital literacy, economic impact, and social empowerment. The results showed a significant increase in digital literacy from 1.8 to 3.9 (116.7%), with an economic impact in the form of an average increase in MSME income of 110.3%. The program, implemented in three phases—digital infrastructure development, capacity building, and mentoring—successfully transformed 45 MSMEs into digital businesses and increased tourist visits by 175.6%. The Cost-Benefit analysis showed high feasibility with a BCR of 3.92 and a payback period of 2.8 months. The social transformation was marked by an increase in women's participation from 28% to 56% and the emergence of 7 digital youth groups. The Village-Owned Enterprise-based platform model generated sustainable revenue of IDR 34 million/month. The study concluded that digital transformation with a holistic approach—integrating technological infrastructure, capacity building, and participatory governance—can be a catalyst for inclusive economic development and sustainable tourism development, offering a blueprint for replication in other tourism villages.